Bifunctional Hierarchical Zeolite‐Supported Silver Catalysts for the Conversion of Glycerol to Allyl Alcohol. Issue 12 (15th March 2017) - Lari, Giacomo M.; Chen, Zupeng; Mondelli, Cecilia; Pérez‐Ramírez, Javier
Abstract: The establishment of suitable processes for the conversion of glycerol into allyl alcohol is hindered by the fast deactivation of solid acids in the dehydration of the substrate to acrolein and by the requirement of hydrogen donors to enhance the selectivity of the subsequent reduction step. In this work, silver nanoparticles deposited onto a hierarchical ZSM‐5 zeolite are proved to be an effective bifunctional catalyst to conduct the two reactions in the gas phase and in the presence of hydrogen by using a continuous fixed‐bed reactor. The acidic function was accomplished by using a ZSM‐5 zeolite modified by facile alkaline and acid treatments, which decreased the amount of Lewis acid centers while preserving the amount of Brønsted acid centers, and introduced an auxiliary network of intracrystalline mesopores, thus boosting the selectivity to acrolein (62 %) and the resistance to coking. Upon screening of various metals supported on the aluminosilicate, silver was identified as a superior hydrogenation catalyst, enabling a relatively high activity with >50 % allyl alcohol selectivity. Tuning of the metal loading, temperature, pressure, and contact time led to 15 % yield of allyl alcohol, thus approaching the state‐of‐the‐art transfer hydrogenation systems, and stable behavior for 100 h on stream. Our results highlight the advantage of conducting the two transformations over a bifunctional material rather than over two separate single‐function solids. Abstract : Coupling of Components : The conversion of glycerol into allyl alcohol is efficiently catalyzed by a bifunctional catalyst comprising silver nanoparticles supported on a hierarchical ZSM‐5 zeolite. This material combines the high stability of the zeolite and the remarkable selectivity of the metal for the dehydration and hydrogenation steps, respectively.